Anthropogenic disturbance of natural forest vegetation on calcareous soils alters soil organic matter composition and natural abundance of 13C and 15N in density fractions - Llorente, Mireia; Glaser, Bruno; Turrión, María-Belén (European Journal of Forest Research, 2010)
In the last century, many calcareous soils in Castilla Leo´n (northwestern Spain) have been transformed from natural Quercus ilex forest to cropped land. Reforestation with Pinus halepensis has been taking place during the past 40 years. In order to obtain a better understanding of how these disturbances affect ecosystem functioning, we studied the quantity and quality of soil organic matter (SOM) in natural forest ecosystems, cropland and Pinus plantations. Density fractionation combined with ultrasonic dispersion enables separation and study of SOM fractions: free organic matter (OM), OM occluded into aggregates and OM stabilized in organo-mineral complexes, considered on the basis of the type of physical protection provided. We separated SOM density fractions and determined the concentrations of C and N, C/N ratios and the natural isotopic abundance (d 13 C and d 15 N values). Transformation of Quercus forest to cropland resulted in major losses of SOC and N, as expected. However, subsequent reforestation with Pinus resulted in good recovery of the original SOC and soil N pools. This indicates the potential for enhanced C storage in agricultural soils by their reversion to a forested state. Study of the density fractions and their 13 C and 15 N signatures enabled better understanding of the high stability of OM in calcareous soils, and analysis of d 13 C variations throughout the proﬁle also enabled identiﬁcation of past C3/C4 vegetation change. Despite the different OC contents of soils under different land use, OM stabilization mechanisms were not signiﬁcantly different. In calcareous soils, accumulation of SOC and N is mainly due to organo-mineral associations, resulting in physicochemical stabilization against further decomposition.
Keywords: 13C; 15N; density fractions; Land use change